How do scientists promoting genetically modified seeds in Africa build trust? The experience of Ghanaian Farmers - Joseph Opoku Gakpo; Katherine McKee (Journal of International Agricultural and Extension Education, 2025)
The use of genetically modified organism (GMO) technology in food systems continues to generate considerable controversy globally. Similar controversies have accompanied the introduction of genetically modified (GM) cowpea, which its developers say has inherent resistance to Maruca vitrata pest attacks, in Ghana. In light of the controversy surrounding the technology and the heavy international donor involvement in the development of the seeds, this qualitative study sought to understand how the scientists who introduced GMOs in Ghana gained the trust of farmers. We found that specific characteristics of the farmers, specific characteristics of the scientists, and the actions that scientists took in their engagement with farmers, were the three key determinants that encouraged trust. The Ghanaian cowpea farmers had inherent characteristics such as risk tolerance and high confidence in intermediaries. These made them predisposed to trusting the scientists. The scientists were effective messengers of the technology, worked with a reputable institution, and showed practically how the technology works. We recommend future GMO dissemination initiatives in Africa be public sector led, in partnership with private sector. We also observe that farmers are less receptive to the linear model of technology transfer and encourage African scientists to use interactive networking approaches if they want to build more trust with farmers on adoption of technologies.
Keywords: GMOs; Farmers; Scientists; Science Communication; Trust; Africa; Ghana